Characterization of tuberose genotypes through DUS testing - TRIVEDI, SARYU; CHAWLA, S.L.; PATEL, A.I.; BHATT, DIPAL; SINDHA, MALLIKA (Journal of Ornamental Horticulture, 2024)
Tuberose (Agave amica L.) is a very selective and unique ornamental bulbous plant admired for the beauty and scent of its blossoms. As there is considerable misunderstanding in the nomenclature of genetic material existing in various Indian states because they are solely referred to as one genotype and all local duplicates are most likely from another. Apart from registration (patents) and commercial introduction of new kinds, the main focus at the moment is to maintain their purity. As a result, an attempt was undertaken to characterize 28 tuberose genotypes in order to produce identifying keys that are reliable and reasonably straightforward to conduct when applying DUS (distinctness, uniformity and stability) testing. However, distinct differences were noticed in floral characters and vegetative character. The study on tuberose genotypes has successfully demonstrated that all the genotypes differed significantly, which makes the candidate variety eligible to seek protection in future. The present study therefore provides very useful leads for future research efforts in this direction.